13910C>T and 22018G>A LCT gene polymorphisms in diagnosing hypolactasia in children - Tomczonek-Moruś, J (United European Gastroenterol J, 2018)
BACKGROUND: Primary lactose intolerance (PLI) is a gradual decrease of lactase activity that usually manifests at the age of 1–5 years. It has been proved that PLI is related to a single-nucleotide polymorphism of the lactase (LCT) gene. OBJECTIVE: An evaluation was performed on the usefulness of genetic tests in detecting LCT 13910C>T and 22018G>A polymorphisms in diagnosing lactose intolerance in children. METHODS: The study group included 99 children aged from 2 months to 16.5 years with different digestive tract symptoms. In all patients a hydrogen breath test (HBT) was conducted and blood samples were collected to determine LCT polymorphisms. PLI was defined as the presence of the 13910CC and/or 22018GG polymorphism in patients with a positive HBT result. RESULTS: In the group younger than 6 years, no statistically significant correlation was observed between the 13910CC and/or 22018GG LCT polymorphisms and HBT result. In the group of children older than 6, a statistically significant correlation between the 13910CC (p = 0.0011) and 22018GG (p = 0.003) LCT polymorphisms and HBT result was detected. CONCLUSIONS: In children older than 6, the result of genetic testing based on LCT 13910C>T and 22018G>A polymorphisms may diagnose lactose intolerance.